KEPEMIMPINAN DALAM BIROKRASI PELAYANAN PERIZINAN USAHA (Suatu Studi Pada Kantor Pelayanan Perizinan Terpadu Kabupaten Minahasa Utara) - TUMBUAN, JESIKA; KIYAI, Burhanuddin; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTAs a means of clear government bureaucracy may not be neutral on the influencegovernment.will but this does not mean that the bureaucracy does not independence.preciselybecause of his duties as a government that works for the interests of this community then in need ofindependence bureaucracy.therein lies the art of bureaucracy it self in repositioning it self.Independence of the bureaucracy can be explained by the influence of governmentneutralit,although the bureaucracy it self is a tool for the government.The criterion is the extent towhich the bureaucracy can be in favor of the community and serve the (publik service).Thus thelack of neutrality mentioned.bureaucracy still have the independence fungsional,yes it is serve theinterests of society as a function of the overall.bureaucracy puts him self more as a public servantthat the servant of the state or at least there is to address the phenomenon of the bureaucraticphenomenon it is necessary to do substantial changes to â€œanatomyâ€ bureaucracy publik inindonesia so as to realize the bureaucracy that is able to adapt with changes in the strategicenvironment is so fast.moreover,for a district in the city of regional autonomy which requires themidependently to regulate and manage the household alone in the midst of global compettion andincreasing public awareness of the true role of the state bureaucracy ,namely the governmentbureacracy that is alwasys ready to provide quality service to the publik.Keyword : Leadership, Bureaucracy, Service